Mine Ground Disaster Monitoring Based on Geosensor Networks - Wang, Jianmin; Zhang, Yongzhan (International Journal of Online and Biomedical Engineering (iJOE), 2015)
Sensor network technology is one of the most promising technologies in the high technology field. Building integrated multi-sensor disaster monitoring system based on sensor network technology is the main direction of the intelligent disaster monitoring technique. The exploitation activities of the mineral resources may lead to geological disasters, so monitoring system needs to speed up the theory and technology innovations, i.e. disaster monitoring, forecasting, early warning and prevention. This paper expounds the concept connotation and key technologies of the geosensor network which contains constructing the unified mining space-time standards, sensor layout principles, and surface disaster monitoring technologies. In addition, the methods of data publication and service in sensor network based on sensor observation service (SOS) are also discussed. It also designs the integral framework of ground disaster monitoring system with SOS. Utilizing the geosensor networks in the ground disaster monitoring system to realize real-time access, cooperative observation, dynamic monitoring, analyzing and predicting the monitoring data will enhance disaster prevention and mitigation capabilities of the monitoring system.